Colloidal Crystals: Three‐Dimensionally Ordered Macroporous Polymeric Materials by Colloidal Crystal Templating for Reversible CO2 Capture (Adv. Funct. Mater. 37/2013). (1st October 2013) - He, Hongkun; Zhong, Mingjiang; Konkolewicz, Dominik; Yacatto, Karin; Rappold, Timothy; Sugar, Glenn; David, Nathaniel E.; Gelb, Jeff; Kotwal, Naomi; Merkle, Arno; Matyjaszewski, Krzysztof
<x xml:space="preserve">Abstract</x> Three‐dimensionally ordered macroporous (3DOM) functional polymeric materials are synthesized by K. Matyjaszewski and co‐workers on page 4720 using colloidal crystal templating. These porous 3DOM materials are successfully used for reversible CO2 capture by humidity swing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>